The Influence of Self Control on Psychological Distress of Prisoners Narcotics in Correctional Institutions Class IIB Narcotics Purwokerto - Asa Fadia Brilian; Ali Muhammad (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem: Incarcerated individuals with a history of narcotics-related offenses often experience elevated levels of psychological distress, which can hinder their rehabilitation process. One contributing factor is the ability, or lack thereof, to regulate self-control, which plays a crucial role in coping with stressors and maintaining psychological well-being. Purpose/Study Objectives: This study aims to analyze the effect of self-control on psychological distress among narcotics inmates at the Class IIB Narcotics Correctional Facility in Purwokerto. Design/Methodology/Approach: The study employed a quantitative research design, utilizing questionnaires to measure levels of self-control and psychological distress. Participants consisted of male inmates currently serving sentences at the facility. Findings: The analysis revealed a significant relationship between self-control and psychological distress. Inmates with higher levels of self-control reported lower levels of psychological distress, underscoring the protective role of self-regulation in reducing mental health problems within correctional populations. Paper Type: Research Article Keywords: Self-Control; Psychological Distress; Correctional Facility; Narcotics Inmates